DEVELOPMENTAL TASKS - Muammar Zulfiqri (Karimiyah: Journal of Islamic Literature and Muslim Society, 2022)
Each developmental phase has a number of developmental tasks that the individual must perform well. This developmental task relates to attitudes, behaviors or abilities that individuals must possess depending on their age or level of development. Islam has informed us about the importance of maintaining and controlling the development of human psychology step by step. Indeed, Islam teaches its people to maintain and maintain the process of human development not only in the prenatal phase, but long before humans become fetuses in the womb. The sources of developmental tasks are: requirements for religious norms, physical maturity, cultural requirements of the community, as well as requirements and proposals and individual efforts. There are at least 6 (six) developmental tasks, namely; Developmental Tasks for Infants and Children, Elementary School, Early Adulthood, Middle Adulthood, and Developmental Tasks for the Elderly This is based on research using scientific methods that may change from time to time, or based on developments in social science.